An Analysis on The Types of English Slang Words Found in Neel + Jordan Podcast - Mulyantini, Ni Putu Eny; Santika, I Dewa Ayu Devi Maharani; Sulatra, I Komang (Institut Pariwisata dan Bisnis Internasional, 2023)
Slang occurs in any language of a region especially when people communicate in informal situations. This study focuses on identifying the types of slang words used by Neel + Jordan on their conversation through a podcast. The data are taken from their podcast on Youtube entitled Australian Culture. This study was done in order to make the viewers of the podcast easier to understand the content. The method conducted is descriptive qualitative. Observation and note-taking techniques are used to collect the data. There are five types of slang as follows: fresh & creative, clipping, flippant, acronym, and imitative based on the theory used from Allan & Burridge (2006). The writer formed the data using a table and conducted a description afterwards in order to make the analysis clear and the readers easy to understand. The result of the study was that there were five types of slang found in the Neel + Jordan Podcast.